Improving the experience of facility-based delivery for vulnerable women through obstetric care navigation: a qualitative evaluation - Kirsten Austad; Michel Juarez; Hannah Shryer; Patricia L. Hibberd; Mari-Lynn Drainoni; Peter Rohloff; Anita Chary (BMC, 2021)
Abstract Background Global disparities in maternal mortality could be reduced by universal facility delivery. Yet, deficiencies in the quality of care prevent some mothers from seeking facility-based obstetric care. Obstetric care navigators (OCNs) are a new form of lay health workers that combine elements of continuous labor support and care navigation to promote obstetric referrals. Here we report qualitative results from the pilot OCN project implemented in Indigenous villages in the Guatemalan central highlands. Methods We conducted semi-structured interviews with 17 mothers who received OCN accompaniment and 13 staff-namely physicians, nurses, and social workers-of the main public hospital in the pilot's catchment area (Chimaltenango). Interviews queried OCN's impact on patient and hospital staff experience and understanding of intended OCN roles. Audiorecorded interviews were transcribed, coded, and underwent content analysis. Results Maternal fear of surgical intervention, disrespectful and abusive treatment, and linguistic barriers were principal deterrents of care seeking. Physicians and nurses reported cultural barriers, opposition from family, and inadequate hospital resources as challenges to providing care to Indigenous mothers. Patient and hospital staff identified four valuable services offered by OCNs: emotional support, patient advocacy, facilitation of patient-provider communication, and care coordination. While patients and most physicians felt that OCNs had an overwhelmingly positive impact, nurses felt their effort would be better directed toward traditional nursing tasks. Conclusions Many barriers to maternity care exist for Indigenous mothers in Guatemala. OCNs can improve mothers' experiences in public hospitals and reduce limitations faced by providers. However, broader buy-in from hospital staff-especially nurses-appears critical to program success. Future research should focus on measuring the impact of obstetric care navigation on key clinical outcomes (cesarean delivery) and mothers' future care seeking behavior.